In-Situ Environmental Gamma Radiation Monitoring at Ramna Thana, Dhaka, Bangladesh: In-Situ Environmental Gamma Radiation Monitoring - Mian, M. S.; Rahman, M. S.; Islam, J.; Sakib, K. N.; Tasnim, M. M.; Yeasmin, S. (Journal of Scientific Research, 2019)
Environmental gamma radiation dose rates were measured using a digital portable Gamma-Scout detector from April-May 2018. For this, total 22 monitoring points (MP) were selected in the outdoor environment in the area of Ramna Thana under Dhaka city. The MPs were marked-out using Global Positioning System (GPS) navigation. The GPS reading of the sampling locations were varied from E: 90o23.568' to E: 90o24.895' and from N: 23o44.031' to N: 23o45.018'. The measured dose rates due to natural radionuclides were ranged from 0.115 ± 0.042 µSv.hr-1 to 0.186 ± 0.051 µSv.h-1 with an average of 0.145 ± 0.044 µSv.h-1. The annual effective dose to the population from outdoor environmental gamma radiation was varied from 0.201 ± 0.073 mSv to 0.326 ± 0.090 mSv with an average of 0.255 ± 0.073 mSv. This kind of study is required to detect the presence of natural radionuclides and artificial radionuclides (if any) releasing from nuclear and radiological facilities in the country or from neighboring countries for normal operations or in case of accident/incident. From this study, it can be concluded that there is no radiation burden to the environment due to man-made sources.